Health interventions to promote light physical activity in children and adolescents with physical inactivity – a review of research progress - Siji WANG; Jian LI; Jiu CHEN; Wenlai CUI; Yibing WANG; Zhe KONG; Jun XIE (Zhongguo gonggong weisheng)
Physical inactivity refers to an individual′s failure to meet the recommended amount of physical activity for their age group as outlined in physical activity guidelines. It is also known as insufficient physical activity. A 2023 survey report found that 86% of children and adolescents in China are physically inactive, posing a serious threat to their physical and mental well-being and to the sustainable development of society′s health. This highlights the urgent need for health interventions targeting physically inactive children and adolescents. Previous studies have focused primarily on the effectiveness of health interventions for physically inactive children and adolescents. While physiological evidence suggests that moderate-to-vigorous physical activity (MVPA) has the most beneficial physiological effects for individual health promotion, research suggests that the effects of such interventions are often not sustained. Conversely, light physical activity (LPA), such as walking and simple stretching, is feasible and acceptable for most physically inactive children and adolescents and serves as a critical driver for promoting their sustainable personal health development. This study systematically reviews relevant domestic and international research on LPA interventions for physically inactive children and adolescents, aiming to provide a basis for exploring intervention strategies adapted to the sustainable health development of physically inactive children and adolescents in China.